Data management for NREL and beyond: a roadmap and recommendations - Kaplan, Nicole E., author; Newman, Greg, author; SGS-LTER, Colorado State University, publisher (Colorado State University. Libraries, 2013)
This report contains a summary of activities lead by Nicole Kaplan, RA, and Greg Newman, Research Scientist, and a strategy for managing data, which were supported by 2012 Program Development Funds at the Natural Resource Ecology Laboratory (NREL). We set out to describe current components, functions and expertise of the NREL cyber-infrastructure and inquire about current work and future needs for managing, archiving and providing access to data. The activities we coordinated included: (1) conducting a workshop, (2) arranging the Spring 2012 seminar series entitled Data Literacy: Bridging the Gap Between Science and Society, (3) contributing to over a dozen data management plans for NREL proposals, (4) providing database services to PHACE (a large collaborative project), and (5) attending conferences and workshops to obtain new ideas and build partnerships. The results of what we learned and accomplished include overall data management goals for NREL, a model for a data management system for NREL, requirements for a web-based data access and delivery system, policies for data sharing and attribution, training for undergraduate and graduate students, and scholarly work in Ecological Informatics (e.g. Chu et al. in press, Newman et al. 2011, Vanderbilt et al. 2009). Our work was presented at the NREL 2012 Annual Retreat and the presentation file is available upon request. Here, we present resources for NREL to plan and conduct data management as part of the research process. We propose a model that establishes a hierarchy of workspaces to support, preserve, and secure the flow of data from the private laboratory space of the Principal Investigator, to a web-based NREL Data Repository to disseminate data to the public and stakeholders. We detail how current cyber-infrastructure capabilities can be leveraged to meet needs within NREL for data management, facilitate research discovery and data re-use, and contribute to NREL excellence. Major benefits to managing, sharing and re-using data include increasing the competitiveness of NREL proposals, influencing expectations of funding agencies for data management, accelerating global change research (Wolkovich et al. 2012), and broadening scientific understanding and services to support decision-making (Dozier and Gail 2009). In addition, federal research sponsors are committed to increasing open access to data and are requiring data management plans from agencies and departments with over 100 million dollars in research and development expenditures (Holdren 2013 and e.g. The Fair Access to Science and Technology Research Act (FASTR).
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Version 1.1 - June 2013.
Keywords: Central Plains Experimental Range; data; artefacts; information infrastructure; access; collaborative team; long term ecological research; shortgrass steppe; grassland ecology; Pawnee National Grassland